Construção de uma balança simples para determinação da tensãosuperficial de líquidos - Reis, T.o. (2015)
In the present work, it is suggested the construction of a balance using low-costmaterials in order to determine surface tension of liquids. The reliability ofthe measurements was confirmed by comparing these results with those reported inthe literature using capillary rise method for simple liquids. In the proposedmethod, the systematic errors from the obtained results obtained with thisdevice are reduced considerably. The principle of the device’s operationconsists of measuring the force required to remove/detach a glass slidepartially immersed in a liquid. The values of surface tension are calculatedbased on concepts of moment of a force (torque) and considering intermolecularinteractions between glass and liquid surface.